Insights into the vaginal microbiome in a diverse group of women of African, Asian and European ancestries - Roachford,Orville St. E.; Alleyne,Angela T.; Nelson,Karen E. (PeerJ, 2022)
Background Intra-continentally, vaginal microbiome signatures are reported to be significantly different between Black and Caucasian women, with women of African ancestry having the less well defined heterogenous bacterial community state type (CST) deficient of Lactobacillus species (CST IV). The objective of this study was to characterize the vaginal microbiomes across a more diverse intercontinental group of women (N = 151) of different ethnicities (African American, African Kenyan, Afro-Caribbean, Asian Indonesian and Caucasian German) using 16S rRNA gene sequence analysis to determine their structures and offer a comprehensive description of the non-Lactobacillus dominant CSTs and subtypes. Results In this study, the bacterial composition of the vaginal microbiomes differed significantly among the ethnic groups. Lactobacillus spp. (L. crispatus and L. iners) dominated the vaginal microbiomes in African American women (91.8%) compared to European (German, 42.4%), Asian (Indonesian, 45.0%), African (Kenyan, 34.4%) and Afro-Caribbean (26.1%) women. Expanding on CST classification, three subtypes of CST IV (CST IV-A, IV-B and IV-C) (N = 56, 37.1%) and four additional CSTs were described: CST VI Gardnerella vaginalis—dominant (N = 6, 21.8%); CST VII (Prevotella—dominant, N = 1, 0.66%); CST VIII (N = 9, 5.96%), resembling aerobic vaginitis, was differentiated by a high proportion of taxa such as Enterococcus, Streptococcus and Staphylococcus (relative abundance [RA] > 50%) and CST IX (N = 7, 4.64%) dominated by genera other than Lactobacillus, Gardnerella or Prevotella (e.g., Bifidobacterium breve and Anaerococcus vaginalis). Within the vaginal microbiomes, 32 “taxa with high pathogenic potential” (THPP) were identified. Collectively, THPP (mean RA ~5.24%) negatively correlated (rs = −0.68, p < 2.2e−16) with Lactobacillus species but not significantly with Gardnerella/Prevotella spp. combined (r = −0.13, p = 0.1). However, at the individual level, Mycoplasma hominis exhibited moderate positive correlations with Gardnerella (r = 0.46, p = 2.6e−09) and Prevotella spp. (r = 0.47, p = 1.4e−09). Conclusions These findings while supporting the idea that vaginal microbiomes vary with ethnicity, also suggest that CSTs are more wide-ranging and not exclusive to any particular ethnic group. This study offers additional insight into the structure of the vaginal microbiome and contributes to the description and subcategorization of non-Lactobacillus-dominated CSTs.
Keywords: Vaginal microbiome; Community state types; CST subtypes; Ethnicity; Ancestries; Lactobacillus; Pathobionts; Mycoplasma; Prevotella; Gardnerella